Relationship of the extended use of hydrochlorothiazide with melanoma: a literature review (Research, Society and Development, 2020)
Recent studies show a strong relationship between the use of hydrochlorathiazide (diuretic and antihypertensive drug) and the risk of developing melanoma due to its photosensitizing feature on the skin. The aim of this paper is to show the association between the use of hydrochlorathiazide and the increased risk of melanoma onset. The methodology was a bibliographic survey with articles published from 2016 to 2019 in the electronic databases of scientific reliability PubMed, Medline, Science Direct and journals specialized in the subject. Four pertinent studies were found on the subject, which identified that hydrochlorothiazide is classified as a carcinogenic drug by the International Agency for Research on Cancer. As exposure to ultraviolet light increases skin cell damage, long-term concomitant administration of hydrochlorothiazide leads to an increased likelihood of skin malignancy, including the development of melanoma. A meta-analysis was performed involving melanoma patients in Denmark. The total study population was 19,273 cases and 192,730 controls; Among these, 413 cases (2.1%) and 3,406 controls (1.8%) were classified as users of high cumulative doses of hydrochlorothiazide (≥ 50,000 mg), resulting in an adjusted odds ratio (OR) of 1.22 for melanoma. Therefore, it is suggested that the use of hydrochlorothiazide is associated with the onset of melanoma. More large studies, mainly national, are needed to confirm the findings. Therefore, the indication that hydrochlorothiazide use increases the risk of melanoma may have clinical relevance related to drug choice, particularly for patients with melanoma risk factors.